An Islamic Religious Education-Based Manners Program in Phase C Public Elementary Schools - Muhammad Ma'sum; Akhmad Alim; Nesia Andriana; Stefan Th. Gries (At Turots: Jurnal Pendidikan Islam, 2025)
Many students still have problems with manners and etiquette, both in their attitudes and behaviour in everyday life. The study aims to develop a manners habit formation programme based on Islamic education at Fase C Public Primary School. The study uses the ADDIE research and development (R&D) approach. The research subjects were teachers, Phase C students, and parents of students. The research findings indicate that the Islamic education-based manners training programme at Phase C Public Elementary School is feasible and practical. The implementation of the manners training programme has a positive impact on improving students' manners.